2015
DOI: 10.1097/cmr.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

IL-17, IL-23, and p73 expression in cutaneous melanoma

Abstract: The incidence of cutaneous malignant melanoma is increasing worldwide, resulting in the demand for clinically useful prognostic biomarkers, especially for invasive and metastatic disease. We studied the immunohistochemical expression of interleukin-17 (IL-17), IL-23, and p73 in 35 malignant melanomas and compared them with benign melanocytic nevi and Spitz nevi, correlating them with clinical-pathological variables. A higher and statistically significant difference (P<0.05) in the intensity and percentage of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…They studied the expression of interleukin‐17 (IL‐17), IL‐23, and p73 in 35 malignant melanomas comparing them with benign melanocytic nevi and Spitz nevi. Their results showed a greater IL‐17 and IL‐23 immunohistochemistry expression in the melanoma group than in ordinary benign nevi . These results could suggest a possible IL‐17, IL‐23, and p73 involvement in cutaneous melanomas with a hypothetical impact on melanoma invasiveness.…”
Section: Il‐17 and Oncological Skin Diseasesmentioning
confidence: 88%
“…They studied the expression of interleukin‐17 (IL‐17), IL‐23, and p73 in 35 malignant melanomas comparing them with benign melanocytic nevi and Spitz nevi. Their results showed a greater IL‐17 and IL‐23 immunohistochemistry expression in the melanoma group than in ordinary benign nevi . These results could suggest a possible IL‐17, IL‐23, and p73 involvement in cutaneous melanomas with a hypothetical impact on melanoma invasiveness.…”
Section: Il‐17 and Oncological Skin Diseasesmentioning
confidence: 88%
“…Additionally, IL-17/IL-17RA pathway stimulated cell proliferation of mouse B16F10 and human A375 and A2058 cell lines ( Chen et al, 2019 ). IL-17 and IL-23 immunohistochemistry expression were increased in the melanoma tissues, possibly enhancing VEGF expression and angiogenesis ( Ganzetti et al, 2015 ). Therefore, these analyses supported the hypothesis of the importance of hypoxia microenvironment in the regulation of the biological behavior of tumor cells and surrounding non-tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al [8] also reported that TP73 was overexpressed in cervical cancer tissues compared with normal cervical tissues. In addition, high expression of TP73 was suggested in several kinds of human tumors such as breast cancer [15,16], esophageal cancer [17], thymic carcinoma [18], extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [21,22], gastric cancer [23,24], colorectal cancer [25–27], ovarian cancer [28], laryngeal cancer [29], parotid gland carcinoma [30], cutaneous melanoma [31] and retinoblastoma [32]. However, low TP73 expression was observed in bladder cancer and head and neck squamous cell carcinoma, compared to corresponding normal tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%